Affordances and effects of introducing social media within eParticipation—Findings from government‐initiated Indonesian project. Issue 4 (26th June 2018) - Dini, Alfatika Aunuriella; Sæbo, Øystein; Wahid, Fathul
Abstract: In this paper, we explore "LAPOR!, " a government‐developed social media project within a young democratic society. LAPOR! is a system for citizens to report various issues to the public and represents a novel example of a custom‐made tool by the Indonesian government. We examine the system's action potentials, constraining factors, and effects identified through the lenses of the technology affordances theory. LAPOR! introduces different affordances that influences citizens' level of engagement compared with mainstream social media. We contribute by fostering a better understanding of the development of custom‐made social media initiatives. Moreover, we contribute knowledge to the field by investigating eParticipation projects from emerging economies, such as Indonesia, a context that has not been thoroughly investigated.